Research for sustainable agricultural production systems in high altitude zones of Eastern Africa - Wortmann, Charles S. (International Center for Tropical Agriculture, 1993)
Demands for food and fiber are increasing at a faster rate than supply in the medium and high altitude zones of Eastern Africa, while the productivity of the land is apparently declining. In many cases, productivity is constrained primarily by insufficient nutrient supply. To meet future demands for food, the land`s productivity will need to be maintained, or rejuvenated, and managed for greater productivity. Sustainable agricultural systems which allow for increased production need to be developed and implemented. This paper explores a number of issues relevant to research for sustainable agriculture in Eastern Africa and proposes an alternative research approach. The need and place for both high-input and low-input production systems is explored. Roles of alternative research methodologies, including commodity and disciplinary, farmer participatory, agro-ecological and eco-regional methodologies are discussed. The challenge of improving agricultural production in a sustainable manner for a wide range of micro-environments is addressed. Promotion of technologies, especially when packages of practices or novel systems are needed, is discussed. A research approach is proposed which is based on intensive farmer participatory research in carefully selected farming communities. The communities serve as benchmark research "sites" of larger agro-ecological zones, with consideration of socio-economic factors. Various research methodologies are applied at the various stages of the research process.